189 Comparison of Efficacy of Tonic and Burst Occipital Nerve Stimulation in Treating Trigeminal Allodynia: Chronic Result. (August 2016) - Clark, Shannon Wang; Venkatesan, Lalit; Boorman, David; Fried, Nathan; Oshinsky, Michael; Sharan, Ashwini Dayal; Elliott, Melanie
Abstract : INTRODUCTION: Burst stimulation is a new paradigm that eliminates paresthesias typically observed with traditional tonic stimulation. We used a rodent model of episodic migraine to compare the efficacy of tonic and burst stimulation in treating trigeminal allodynia. METHODS: Twelve Sprague-Dawley rats with spontaneous trigeminal allodynia1 were implanted with miniaturized paddle leads over the occipital nerves, and the leads connected to a pulse generator located dorsally. Rats were randomly assigned to receive 4 frequencies: tonic 60 Hz, tonic 500 Hz, burst 40 Hz, and burst 50 Hz. Tonic 500 Hz and burst 50 Hz were the most effective parameters on short-term trials conducted previously. Tonic 60 Hz and burst 40 Hz are the most common parameters in clinical use. After establishing baseline hypersensitivity, the stimulation was turned ON for 10 days, followed by OFF for 10 days. Daily periorbital sensitivity was assessed using von Frey filaments (VFF). Rats were characterized as hypersensitive or as responders when VFF thresholds were 4 g or 6 g, respectively. Analysis of variance tests were used for analysis. RESULTS: Overall, both tonic and burst ONS significantly improved VFF thresholds compared with baseline ( P < .005). Tonic stimulations had a superior response ( P = .022) on day 1, but the burst stimulations produced superior efficacy from day 3. On 3, 4, 6, and 9 of ON days, there were statistically superior reduction of allodynia observed for burst stimulations. After the stimulation was turned OFF on day 10, tonic stimulations lost efficacy sooner, whereas burst stimulations had a trend in maintaining superior efficacy for an additional day (day 11, P = .053). CONCLUSION: Tonic stimulation had superior take-off efficacy, but there was a latent positive response associated with burst stimulation that made it superior to tonic stimulation. In addition, burst stimulations exhibited a better therapeutic carryover effect that lasted for a day after stimulation was OFF. Human trials of burst stimulation for headache disorders are warranted to clinically validate our results.